Pembrolizumab-Induced Lichen Planus Pemphigoides in a Patient with Metastatic Adrenocortical Cancer: A Case Report and Literature Review - Vrinda Madan; Mark C. Marchitto; Joel C. Sunshine (MDPI AG, 2023)
While the advent of immune-checkpoint inhibitors has revolutionized cancer therapy, immune-related adverse effects (irAEs) have also been on the rise. Cutaneous toxicities are among the most common irAEs, especially in the context of programmed cell death protein-1 (PD-1) inhibitors like pembrolizumab. Herein, we report a case of anti-PD-1-induced lichen planus pemphigoides (LPP)-a rare autoimmune blistering disorder with characteristics of both lichen planus and bullous pemphigoid. To our knowledge, this is the first reported case of LPP following anti-PD-1 therapy for metastatic adrenocortical cancer. Recognizing that LPP is within the spectrum of irAEs is important, especially as the indications for immunotherapy grow to include rarer malignancies like adrenocortical cancer. In addition to our case presentation, we also provide a comprehensive review of the literature surrounding immunotherapy-induced LPP-highlighting key characteristics towards the early recognition and clinical management of this cutaneous irAE.